Women in Academia and Research: An Overview of the Challenges Toward Gender Equality in Colombia and How to Move Forward - Franco-Orozco, Carolina M.; Franco-Orozco, Bárbara (Frontiers in Astronomy and Space Sciences, 2018)
Throughout history and over the last years, women have strongly intended to play central roles in addressing major aspects of the world’s most urgent problems such as global poverty, health and climate change. Women have been in a continuous effort to promote health, educational and environmental sustainability programs. In exchange, women are facing countless obstacles to ensure gender equality. Colombia has until recently been highly affected by decades of violent armed conflicts. Today, peace processes are having considerable success on solving these conflicts, but several social problems still persist. One of these problems is gender inequality that systematically hampers the ability of women to progress and develop their full potential. This reborn Colombia following the peace negotiations, should be the key for having a country where men and women are treated equally and with justice. Instead women rights are still being continuously affected by violence, social exclusion, exploitation and discrimination. Gender inequality creates a big barrier that needs to be overcome by women that want to effectively contribute to a so necessary development of Colombia. Science is not an exception on the field of gender-equality, being a great disparity between men and women present in the Colombian scientific community. In this review we discuss the hurdles that scientific women face in Colombia. Furthermore, and by learning from the experiences of some successful female Colombian Scientists, we shed new lights on how women can overcome these challenges. We will also show how these female scientific leaders from different disciplines have combined efforts to build a better country with regards to science, education, technology and innovation. Lastly, we propose new ways to reach gender equality in the scientific community. We hope that this review will motivate many young female scientists to invest in their careers, and ultimately help in the social development of Colombia.